A Study of the Atheist View on Religion - Rohmawati, Hanung Sito (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2022)
Abstract: Religion is not always glorified like religious adherents glorify it. Moreover, scientific and technological progress has given birth to a new spirit of autonomy and independence that has encouraged most people to declare freedom from God. Atheists offer a concept in the form of freedom to have no religion at this time. And atheism has become a trend in the West, atheism that has developed in the West is not just a Western issue or program in various fields such as politics, economics and culture. Therefore, it is important to study to see the perspective of religion. In this article, the author only describes three influential atheists in the early 21st century. Namely Richard Dawkins, Christopher Hitchen and Sam Harris. The three figures have phenomenal works in and the existence of God. Although the three figures mentioned above are religious critics, there will be differences between them. Richard Dawkins is more concerned with the problem that religion is a delusion, Hitchen criticizes religion in terms of religious institutions. While Harris criticizes religion in terms of the things that religion has to offer, for him religion does not offer peace but the opposite. Abstrak: Agama tidak selamanya dimuliakan seperti para penganut agama memuliakanya. Apalagi kemajuan sanis dan tekhnologi melahirkan semangat autonomi dan independensi baru yang mendorong sebagian orang untuk mendeklarasikan kebebasan dari Tuhan. Kalangan ateis menawarkan konsep dalam bentuk kebebasan untuk tidak memiliki agama pada saat ini. Dan ateisme telah menjadi tren di tren bagi orang Barat, ateisme yang berkembang di Barat bukan hanya sekedar isu atau program Barat di berbagai bidang seperti bidang politik, ekonomi dan kebudayaan. Oleh karena itu penting dikaji untuk melihat cara pandang ateis terhadap agama. Dalam artikel ini penulis hanya menjabarkan tiga tokoh ateis yang berpengaruh pada awal abad ke-21. Yaitu Richard Dawkins, Christopher Hitchen dan Sam Harris. Ketiga tokoh tersebut mempunyai karya-karya fenomenal dalam menentang keberadaan Tuhan. Meskipun ketiga tokoh yang disebut di atas merupakan pengkritik agama, akan tetapi ada perbedaan antara mereka. Richard Dawkins lebih ke persoalan bahwa agama merupakan delusi, Hitchen mengkritik agama dari segi institusi agama. Sedangkan Harris mengkritik agama dari segi ha-hal yang ditawarkan oleh agama, baginya agama itu tidak menawarkan perdamaian akan tetapi sebaliknya.